Survey of the causes of failure among education students - Diaz, Sotera F. (2009)
The study attempted to find out the causes of failure among Education students. It involved sixty-four students who failed in one or more subjects in the first semester of SY 2008-2009. It identified seven major causes such as: (a) difficulty of subjects and tests, (b) high passing score, (c) financial problems, (d) difficulty of understanding teacher's explanation, (e) course not their choice, and (f) noisy boarding house. Subject teachers may make use of varied methods and techniques to facilitate understanding and look into the degree of difficulty of test items. Academic administrators may review the grading system.
Keywords: Rating of students